Experiments with young nidifugous birds on a visual cliff - Kear, Janet (Wildfowl, 1967)
Newly-hatched young of ground-nesting species were found to prefer the shallow side of a visual cliff, while birds normally hatching in holes in trees chose the shallow and deep sides about equally. Species which nest both on the ground and in trees gave intermediate scores. The reaction of the hole-hatching ducklings was definite enough to suggest that their performance was not due to inferior powers of depth discrimination; it possibly represented a compromise between a wide-spread tendency to avoid sharp drops and the necessity for jumping to the ground soon after hatching.